2018
DOI: 10.1186/s13017-017-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Casualties of peace: an analysis of casualties admitted to the intensive care unit during the negotiation of the comprehensive Colombian process of peace

Abstract: BackgroundAfter 52 years of war in 2012, the Colombian government began the negotiation of a process of peace, and by November 2012, a truce was agreed. We sought to analyze casualties who were admitted to the intensive care unit (ICU) before and during the period of the negotiation of the comprehensive Colombian process of peace.MethodsRetrospective study of hostile casualties admitted to the ICU at a Level I trauma center from January 2011 to December 2016. Patients were subsequently divided into two groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
7
0
3
Order By: Relevance
“…Among these, 351 articles were excluded after title screening and the abstract of the 784 remaining papers was assessed. Finally, 461 publications were excluded following the eligibility criteria and thus, 323 articles that had interpretable data and fulfilled the eligibility criteria were used for data extraction…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 351 articles were excluded after title screening and the abstract of the 784 remaining papers was assessed. Finally, 461 publications were excluded following the eligibility criteria and thus, 323 articles that had interpretable data and fulfilled the eligibility criteria were used for data extraction…”
Section: Resultsmentioning
confidence: 99%
“…The peace process was successful in reducing violence and de-escalating the conflict during the four years of negotiations (CERAC, 2016;Ordoñez et al, 2018). A bilateral ceasefire between FARC and the government was put in place in August of 2016, when a final accord between the two parts was announced.…”
Section: Historical Contextmentioning
confidence: 99%
“…Manuel Santos, president 2010-2018, and Álvaro Uribe, president 2002 and current senator, both active Twitter users representing polar sides of the political debate regarding the peace negotiations with the rebel group (that is, what I refer to as the "left-wing" and the "right-wing" positions). 4 I find evidence for both the rally 'round the flag and the increased right-wing support effects.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, the Departamento Administrativo Nacional de Estadistica (DANE) 12 reported that the trauma is the main cause of death among young adults and the second leading cause of death in general population with a total of 34,216 deaths in 2007. 54% of all patients who died between 1998 and 2011, were considered to died due to preventable causes, the most common trauma mechanism was gunshot wounds, followed by stab wounds, and traffic road accidents 12,13 . The 50% of patients with severe hemorrhage do not receive timely healthcare and die before hospital admission.…”
Section: Epidemiologymentioning
confidence: 99%
“…Las tasas de mortalidad fueron más altas en países de bajos ingresos, principalmente debido a accidentes de tránsito. En Colombia, de acuerdo con el Departamento Administrativo Nacional de Estadística (DANE) 12 , El trauma es la principal causa de muerte en adultos jóvenes y la segunda causa de muerte en general en la mayoría de las ciudades de Colombia, el DANE estimo en 34216 muertos por trauma en 2007.El Instituto Nacional de Salud de Colombia (INS) consideró que el 54% de todos los pacientes que murieron entre 1998 y 2011 eran prevenibles; de este porcentaje, la mayoría se debieron a heridas por armas de fuego, seguido por armas cortopunzantes y accidentes automovilísticos 12 , 13 .…”
Section: Introductionunclassified